2020
DOI: 10.3390/nu12092868
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of the Operationalization of Fruit and Vegetable Variety

Abstract: Adequate consumption of fruits and vegetables is critical for healthy growth and development. Less is known about fruit and vegetable variety, with variation in operationalization of variety. This review aims to identify currently available evidence operationalizing fruit and vegetable (FV) variety through a scoping review to summarize, compare, and critically evaluate the operationalization of variety. A secondary aim is to examine the implications of measuring FV variety and outcomes including dietary qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
(540 reference statements)
0
12
0
Order By: Relevance
“…Another scoping review by Marshall and colleagues10 (2020) included just over 400 articles to reveal how fruit and vegetable variety has been operationalised. Looking only at the variety of fruits and vegetables, the researchers found that nearly all 51 included studies had different definitions of variety which makes it difficult to compare findings 10.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another scoping review by Marshall and colleagues10 (2020) included just over 400 articles to reveal how fruit and vegetable variety has been operationalised. Looking only at the variety of fruits and vegetables, the researchers found that nearly all 51 included studies had different definitions of variety which makes it difficult to compare findings 10.…”
Section: Introductionmentioning
confidence: 99%
“…Another scoping review by Marshall and colleagues10 (2020) included just over 400 articles to reveal how fruit and vegetable variety has been operationalised. Looking only at the variety of fruits and vegetables, the researchers found that nearly all 51 included studies had different definitions of variety which makes it difficult to compare findings 10. Given the growing interest in DD in recent years, an updated and more comprehensive scoping review on the measurement of DD beyond the variety of only fruits and vegetables is warranted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Associating each color with a health benefit is a simplified strategy designed to: (1) help individuals relate to the health properties of FV, (2) promote greater recognition of their importance, and (3) increase the diversity of FV colors consumed across all life stages [15]. Despite these campaigns, assessment of FV variety in both clinical practice and research has been typically based on the number of individual types of FV a person consumes rather than assessing variety of bioactive pigments [18,19]. Observational studies have shown that FV intakes, grouped by their color, are associated with improvement in a range of health outcomes including cognitive decline, cardiovascular disease (CVD) and colorectal cancer [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…According to a scoping review summarizing the operationalization of FV variety [ 11 ], many studies have used a food frequency questionnaire (FFQ) or 24-h dietary recall (24-h recall) to measure FV variety. In general, an FFQ is intended to comprehensively assess the amount of nutrients and foods consumed [ 12 ] and is less likely to be developed with the intention of measuring FV variety.…”
Section: Introductionmentioning
confidence: 99%